Careers patterns in Greek academia: social capital and intelligent careers, but for whom?. Issue 3 (3rd June 2014) - Bozionelos, Nikos
Abstract : Purpose: – The purpose of this paper is to develop a comprehensive account for careers within the Greek academic system. Historical, cultural and geographical features of the country have created a unique context that has shaped the way academic careers evolve. Design/methodology/approach: – The primary methods of data collection were retrospective participant observation and discussions in interview form with individuals who have had various types of experience with the Greek Higher Education system. Findings: – The major factor that shapes careers in Greek academia is social capital or know-whom that operates within a broader cultural environment where institutional collectivism is extremely low, the in-group – out-group distinction is a major element, and political party affiliation plays a key role in everyday affairs. As a result academic careers in Greece are almost exclusively determined by membership, a priory or earned, to an "in-group" that is linked via blood, family friendship, business and political party ties. This "in-group" uses its social capital to control academic careers across all stages for the benefit of its members. Research limitations/implications: – There are method limitations, but relevant concerns were largely alleviated by precautionary measures and the way data were utilized. Ethnography may be the most appropriate method to disentangle the way networks and social capital impact careers. Practical implications: – Achieving substantive change, such as increasing meritocracy, within a sector may be impossible without considering the broader cultural context that encapsulates it. Originality/value: – The study is among the very first to unveil the "dark side" of social capital, and show how social capital may benefit the interests of in-groups at the expense of the collective.